CONTROVERSIES ON VERTEBROPLASTY AND KYPHOPLASTY FOR VERTEBRAL COMPRESSION FRACTURES - Teles,Alisson Roberto (2015)
Vertebroplasty and kyphoplasty are widely used for osteoporotic and cancer-related vertebral compression fractures refractory to medical treatment. Many aspects of these procedures have been extensively discussed in the literature during the last few years. In this article, we perform a critical appraisal of current evidence on effectiveness and ongoing controversies regarding surgical technique, indications and contraindications, clinical outcomes and potential complications of these procedures.